Length-weight relationships of eighteen species of freshwater fishes from Panchet Reservoir in Ganges basin, Jharkhand, India - Sandhya, K.M.; Karnatak, Gunjan; ., Lianthuamluaia; Sarkar, Uttam Kumar; Kumari, Suman; Mishal, P.; Kumar, Vikash; Panda, Debabrata; Ali, Yousuf; Naskar, Bablu (Indian Journal of Fisheries, 2020)
The present study describes the length-weight relationships (LWRs) of 18 fish species from a large tropical reservoir, Panchet, in the Damodar River basin, one of the main tributary of the largest river Ganga in India. A total of 2419 individuals represented by 18 species belonging to 9 families were sampled between November 2014 and June 2016. The b values ranged from 2.469 for Trichogaster chuna to 3.428 for Ailia coila. All the regressions were highly significant (p<0.001). The results revealed positive allometric growth for seven species (b>3, p<0.05), negative allometric growth for seven species (b<3, p<0.05) and isometric growth for four species (b=3, p>0.05). This study represents the first reference on the length-weight relationship of Trichogaster chuna from a reservoir ecosystem. This is the first report on LWRs of five fish species viz., Puntius terio, Pethia conchonius, Sperata seenghala, Ailia coila and Trichogaster chuna from an Indian reservoir. This study provides basic data for future stock assessment studies and management programmes from Panchet Reservoir as well as for complementing the comparisons of LWRs from other ecosystems. Keywords: Growth, Length-weight relationships, Panchet, Reservoir, Stock assessment